Influence of Instrumental Motivation and Integrative Motivation on English Learning Outcomes - Wisnuwardhani, Sitaresmi Imaniyati (Research Collaboration Community (Rescollacom), 2022)
This research addresses students’ motivation in influncing learning outcomes. The purpose of this study is to describe the students’ condition of motivation in learning English whether it tends to be integrative or instrumental and the extent to which their motivation in learning English may influence students’ learning outcome. This research was conducted based on principles of qualitative research. The researcher conducted an online interview to collect the data. The mid-term test grade are used as the learning outcome. Data gained in the interview and Mid-term test grade were compared and then analyzed it descriptively. Population of this study are students at grade nine. It is about 29 students in a class. The result performs that students in learning English were motivated by both instrumental and integrative motivation. That is motivation to have wider social contact with target language speakers and also motivation to utilize English as a tool to gain certain goals like good grade or future goals. Based on the findings, it is suggested that the teacher should able to motivate the students’ in learning through developing his/her teaching materials concerned with integrative and instrumental motivation to motivate students’ in learning English